Community Empowerment Together, Know the Spread and Prevention Of Covid 19 - Rita Kartika Sari; Putri Rokhimah Ayuningtyas; Muhammad Agus Supriyono; Citra Primavita Mayangsari; Setyo Trisnadi (Jurnal Health Sains, 2023)
The new world is faced with a health problem, namely the new coronavirus disease pandemic (Corona Virus Disease-2019), caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). This disease was first discovered in December 2019 in the City of Wuhan, Hubei Province, China. This disease can manifest from mild respiratory disorders to severe pneumonia which causes death, this is a global challenge. In March 2020, the World Health Organization (WHO) declared Covid-19 a pandemic, meaning that the disease has spread over a large area, for example several continents, or worldwide. Although intensive research efforts around the world have been carried out, among others related to the prevention, spread and also treatment of Covid-19. Government policies and community participation in efforts to deal with the pandemic are very influential in preventing the spread of the Covid-19 virus. In the context of handling the Covid-19 pandemic, in addition to the government's vaccination program, it also recommends maintaining distance, wearing masks, and washing hands as a preventive measure. The aim of this research is to empower the community to recognize the spread and prevent COVID-19 at the UPT Puskesmas Jenawi, Karanganyar Regency. Place of Implementation at the Karanganyar Jenawi Health Center. Implementation time March 14, 2022 Method: Implementation of activities using a group-based method which is carried out in a comprehensive manner, starting from coordination with policy makers at the Jenawi Health Center, approaches and coordination with the community, educating the community, mentoring, and discussions. The activities of the community service team are carried out in a measurable and monitoring and evaluation process to measure achievement of targets and outcomes, through the role of the community, cadres and puskesmas so that they can improve the health status of the community. The sample is 40 respondents with purposive sampling technique. The results of the implementation of education in the community gain knowledge and insight about Covid 19 so that the community can be empowered to participate in the prevention of Covid 19. The community needs to be vigilant and protective of this global pandemic by knowing its prevention and spread so it is necessary to empower the community and cadres to participate in preventing covid-19 19 through community service by involving competent experts, namely experts in the field of medicine, public health experts, psychologists providing knowledge to the community related to the spread and prevention of the Covid 19 virus.